FLEXURAL TOUGHNESS AND IMPACT RESISTANCE OF PYROLISED RECYCLED STEEL FIBER REINFORCED CONCRETE (International Journal of Engineering Sciences & Management Research, 2017)
Concrete’s role as a building material still continues, unparalleled in this modern era. Current population explosion and the demand for increased standard of living has fueled mankind’s ever-growing commitment in building structures. In this regard, the prospect of utilizing environmentally friendly ingredients should always be prioritized, especially if such option has proved to be economically feasible. In this research, the fiber-reinforcing material obtained from recycled tyres is adopted to further analyze its role in improving the mechanical properties such as flexural toughness, energy absorption and impact resistance. In such pursuit; 39 concrete mixes with 0.5%, 1.0% and 1.5% volume of fibers; and a fiber length of 20mm, 40mm and 60mm were produced to determine the effect of recycled steel fiber on concrete. The main contributions of this paper are: a) characterization of the mechanical properties of recycled steel fiber reinforced concrete in the hardened state b) Measurement of flexural toughness, energy absorption and impact resistance, as the indicators of performance variation between plain and recycled fiber reinforced concrete.